Triggers in L2 Acquisition: the case of Spanish N-N Compounds - Liceras, Juana M.; Díaz, Lourdes (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Spanish has left-headed compounds which are not as productive as their left-headed counterparts in other languages. This presence or absence of productivity has been attributed to a binary parameter according to which N-N compounding, as opposed to nominal constructions in which the head noun takes a complement as in "the destruction of the city”, would be the superset or marked option. Furthermore, the idiosyncratic nature of Spanish N-N compounding has been attributed to the make-up of Spanish Nouns. Specifically, it has been proposed that Spanish Nouns have a ‘word marker’ which triggers L1 acquisition of these constructions. Based on the results of two picture tests intended to elicit actual command of N-N compounding strategies, as well as word order patterns and gender marking patterns, we argue that: 1) N-N compounding is not a marked construction; 2) adult L2 acquisition of Spanish N-N compounds is triggered by head directionality (a processing trigger) rather than by the ‘word marker’ (a representational trigger) which is supposed to trigger L1 acquisition of these compounds.